2016
DOI: 10.1590/1678-4685-gmb-2015-0323
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and arginine vasopressin receptor evolution: implications for adaptive novelties in placental mammals

Abstract: Oxytocin receptor (OXTR) and arginine vasopressin receptors (AVPR1a, AVPR1b, and AVPR2) are paralogous genes that emerged through duplication events; along the evolutionary timeline, owing to speciation, numerous orthologues emerged as well. In order to elucidate the evolutionary forces that shaped these four genes in placental mammals and to reveal specific aspects of their protein structures, 35 species were selected. Specifically, we investigated their molecular evolutionary history and intrinsic protein di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
2
9
0
1
Order By: Relevance
“…Our analyses have shown that OXT , AVP and AVPR1a are under purifying selection. As expected, OXTR seems to be under evolutionary constraint in the set of mammals considered here, corroborating earlier studies ( Paré et al , 2016 ). However, despite this general pattern, there is evidence that OXTR has been under positive selection in some New World monkey branches, where it has coevolved with taxon-specific OXT forms ( Vargas-Pinilla et al , 2015 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our analyses have shown that OXT , AVP and AVPR1a are under purifying selection. As expected, OXTR seems to be under evolutionary constraint in the set of mammals considered here, corroborating earlier studies ( Paré et al , 2016 ). However, despite this general pattern, there is evidence that OXTR has been under positive selection in some New World monkey branches, where it has coevolved with taxon-specific OXT forms ( Vargas-Pinilla et al , 2015 ).…”
Section: Resultssupporting
confidence: 93%
“…Recently, Paré et al (2016) explored the evolutionary forces acting on the four receptors OXTR , AVPR1a, AVPR1b , and AVPR2 in a set of 35 placental mammal orthologs. They found evidence for a dynamic scenario, in which OXTR was under evolutionary constraint, while AVPR1a, AVPR1b , and AVPR2 exhibited elevated rates of evolution, indicating a relaxation of selective pressures, or even positive selection of novel vasopressin receptor variants in the Placentalia ( Paré et al , 2016 ). In the light of these recent findings of the genetic variability of the OXT-AVP system, we aimed to explore whether amino acid changes at AVP, OXT, OXTR, AVPR2, AVPR1a , and AVPR1b could be associated with the animal domestication process.…”
Section: Introductionmentioning
confidence: 99%
“…Arginine vasopressin receptor 1a ( AVPR1a ) is largely expressed throughout the brain (Kantojärvi et al, 2015 ), but also in the liver, kidneys, and vasculature. It is considered to be a crucial receptor for regulation of a set of social behaviors in humans (Ebstein et al, 2009 , 2012 ; Francis et al, 2016 ), such as altruism and social integration (Israel et al, 2008 ; Knafo et al, 2008 ), prepulse inhibition (Levin et al, 2009 ), emotional and cognitive empathy (Israel et al, 2008 ; Knafo et al, 2008 ; Moons et al, 2014 ; Uzefovsky et al, 2015 ; Wang et al, 2016 ), processing and recognition of facial expressions (Israel et al, 2008 ; Knafo et al, 2008 ; Moons et al, 2014 ; Uzefovsky et al, 2015 ; Wang et al, 2016 ) and non-human mammals (Murakami et al, 2011 ; Freeman et al, 2014 ; Paré et al, 2016 ; Lesse et al, 2017 ). Even though vasopressin distribution patterns are quite similar across species, AVPR1a partitions differ both between and within species.…”
Section: Methodsmentioning
confidence: 99%
“…OXTR, AVPR1A , and AVPR1B are genes that emerged evolutionarily through duplication events and have both paralogous and orthologous relationships in placental mammals (Paré et al, 2016). Given their evolutionary connections, roles in social behavior, and potential as treatment target pathways in ASD, we investigated their genetic variation within an ASD population.…”
Section: Introductionmentioning
confidence: 99%